POLICIES FOR REFUGEES AND INTERNALLY DISPLACED PEOPLE IN BOSNIA-HERZEGOVINA. REFLECTIONS ON A STATE UNDER CONSTRUCTION - Figal, Matías (Revista de Historia Social y de las Mentalidades, 2024)
This paper aims to analyze the return policies for refugees and internal displaced persons as a way of approaching to the official discourse in that country. In the face of a war which had as one of its causes the incompatibility of conflicting visions about Bosnia’s statehood, the postwar official discourse is characterized by competence and fragmentation. The analysis of return policies should be understood in the frame of a larger dispute related to the state organization and legitimacy. Besides, it allows to explore both the progress and the predicaments which are still present in Bosnia more than 20 years since the war has ended.